Thermal behavior of ursodeoxycholic acid in urea: Identification of anomalous peak in the thermal analysis - Okonogi S. (2014)
The objective of this study was to clarify the thermal behavior of ursodeoxycholic acid (UDCA) in mixtures with urea. Physical mixtures of UDCA and urea in various ratios were prepared, and the thermal analysis of these sample mixtures was investigated using conventional differential scanning calorimetry (DSC) and variable-temperature powder X-ray diffractometry (VTXRD). The hot-stage microscopy (HSM) and powder X-ray diffractometry (PXRD) were used as complementary techniques. From the DSC results of all sample mixtures, it was found that there was no endothermic peak at the melting temperature of intact UDCA crystals. The DSC thermograms of each ratio showed only the endothermic peak at about 136°C due to the melt of urea and the anomalous endothermic peak at about 155°C-157°C. The VTXRD study revealed that the crystals of urea completely disappeared at a temperature of 140°C. At this temperature, it was identified that the VTXRD pattern obtained was of UDCA crystals. The crystalline peaks gradually decreased in intensity at a temperature of 150°C. When the temperature was up to 160°C, the identical crystalline peaks of UDCA crystals completely disappeared. It was concluded that the anomalous endothermic peak at 155°C-157°C was the peak due to the dissolution of UDCA crystals in the surrounding melted urea.